USING VAGINAL SELF-SAMPLING DEVICES FOR DETECTION OF HIGH-RISK HUMAN PAPILLOMAVIRUS - KRISTINA V. Marochko; NATALIA V. Artymuk; TATIANA Y. Belokrinitskaya; NATALIA I. Frolova (Фундаментальная и клиническая медицина)
The identification of cerval intraepithelial neoplasia is of crucial importance for reducing both incidence and mortality of cervical cancer. Currently, screening programs relying on Papanicolaou test or liquid-based cytology are employed in many countries but have a limited efficiency. Recently, HPV genotyping was suggested as a possible screening alternative as high-risk HPV strains are detected in almost all cervical cancer biopsies. Importantly, in addition to high sensitivity, efficient screening approach also requires a wide population coverage. As the main reasons for cervical cancer screening avoidance include fear of examination, embarrassment, and lack of time, self-sampling devices have the potential to significantly improve screening coverage. Such an approach implies invitation for gynecological examination only if high-risk HPV strains would be detected in the self-collected sample. Epidemiological studies demonstrated that results of HPV genotyping in self- and physician-collected samples are comparable; hence, self-sampling devices can be considered for the implementation in cervical cancer screening.